The Use of Padlet Application to Improve Students’ Writing Skill at the Second Grade of SMPN 30 Padang - Rahma Intan Ditami Haque; Annisha Dyuli Adha; Rahma Dania (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The problems of this research were students students cannot write in a good form, students often do nit remember the general structure of the text well, and cannot find the the right words to write. The research aimed to find out the Impact of Padlet Application on Improving Students’ Writing Skill at SMPN 30 Padang. Padlet is an online tool that allows users to create virtual bulletin boards where they can post various types of content such as text, images, videos, links, and documents. This research used quantitative method with a pre-experimental approach and data collection was carried out using pretest and post test to analyze the effect of using Padlet application on students at SMPN 30 Padang who consisted 33 students from class VIII.I who has choosen using cluster random sampling. The research result show that Padlet application can improve students’ writing skill. The pretest result showed average score was 55,60 and the post test was 70,88. After data was collected, the data was analyzed using t-test formula. The result of the analysis showed that value of t-test > t table is 7,067 > 2,03693. The last hypothesis shows that Ho is rejected and Ha is accepted. It means there is a significant influence on improving students’ writing skill using Padlet application.